Metabolomic Analysis and Mode of Action of Metabolites of Tea Tree Oil Involved in the Suppression of Botrytis cinerea - Xu, Jiayu; Shao, Xingfeng; Li, Yonghua; Wei, Yingying; Xu, Feng; Wang, Hongfei (Frontiers in Microbiology, 2017)
Tea tree oil (TTO), a volatile essential oil, has been widely used as an antimicrobial agent. However, the mechanism underlying TTO antifungal activity is not fully understood. In this study, a comprehensive metabolomics survey was undertaken to identify changes in metabolite production in Botrytis cinerea cells treated with TTO. Significant differences in 91 metabolites were observed, including 8 upregulated and 83 downregulated metabolites in TTO-treated cells. The results indicate that TTO inhibits primary metabolic pathways through the suppression of the tricarboxylic acid (TCA) cycle and fatty acid metabolism. Further experiments show that TTO treatment decreases the activities of key enzymes in the TCA cycle and increases the level of hydrogen peroxide (H2O2). Membrane damage is also induced by TTO treatment. We hypothesize that the effect of TTO on B. cinerea is achieved mainly by disruption of the TCA cycle and fatty acid metabolism, resulting in mitochondrial dysfunction and oxidative stress.